O pai como partícipe no processo da amamentação : intervenção da enfermeira no período gravídico puerperal - Rêgo, Rita Maria Viana (2008)
In Western society, traditionally, the pregnancy experience, education and health of children is part of the tasks that in the sexual division of labor, belongs to the woman. Also in the process of breastfeeding the father is not included. Objective. This study aimed to evaluate interventions in educational practices experienced by couples in the process of breastfeeding having the as a participant. Methodological path. For understanding and description of this phenomenon, the father as a participant in the process of breastfeeding, it was decided to go beyond a situational diagnosis. It was done a research-action considering that the intention has always been dedicated to discuss with the participants of this study, about values, concepts and beliefs culturally assimilated by the society in relation to the process of breastfeeding, and intending to reflect the possible shift in paradigms. Participated eight couples with their children, followed for eight and six months of life. Before the birth, took place four meetings, after the birth of the child, each family was visited daily for ten consecutive days, and, on average, were visited at their residences 20 times in the six months of child´s life. Conclusions. In search of the literature, we found that publications are still incipient and probably actions involving the father in the process of breastfeeding. This experience shows that the father may be an important ally, true partner, is essential to credit and encouraging their participation. They demonstrate satisfaction in providing care to children, especially when they realize that their initiatives and attempts to hit are valued by the partner and by health professionals. It is realized that are shy and isolated the initiatives to include the father, especially in public services, where they are sometimes regarded visits. Recommendations. Facing these results, it is recommended that fathers should be invited to attend meetings and individual consultations of his partner during prenancy and childbirth. Relevance. It is believed that this study will guide motivations to activeness of the nurse to promote the involvement of fathers in the promotion of breastfeeding at the primary level, pre-natal, secondary and tertiary in maternity, continuing in homes of families through domiciliary visits